2016
DOI: 10.1007/s11829-016-9432-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the mycotoxin deoxynivalenol on grain aphid Sitobion avenae and its parasitic wasp Aphidius ervi through food chain contamination

Abstract: We investigated the influence of the Fusarium mycotoxin deoxynivalenol on the English grain aphid Sitobion avenae (Hemiptera: Aphididae) and its parasitic wasp Aphidius ervi (Hymenoptera: Braconidae) using in vitro laboratory experiments. In this tritrophic interaction, deoxynivalenol caused lethal (declined survival) and sublethal (prolonged nymphal development and reduced reproduction) effects on S. avenae aphids and consequentially led to a decreased production of parasitoid offspring resulting from parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…To our knowledge, the few studies investigating the effect of host exposure to insecticides revealed contrasting effects on parasitoid host selection. Whereas host exposure to pesticides may reduce parasitoid attack rate, 49 our results are congruent with studies highlighting a lack of discrimination in terms of parasitoid oviposition behavior between exposed and unexposed hosts 50,51 . Alongside chemical cues, parasitoids use physical traits such as color or shape to locate their hosts 52,53 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…To our knowledge, the few studies investigating the effect of host exposure to insecticides revealed contrasting effects on parasitoid host selection. Whereas host exposure to pesticides may reduce parasitoid attack rate, 49 our results are congruent with studies highlighting a lack of discrimination in terms of parasitoid oviposition behavior between exposed and unexposed hosts 50,51 . Alongside chemical cues, parasitoids use physical traits such as color or shape to locate their hosts 52,53 .…”
Section: Discussionsupporting
confidence: 83%
“…Whereas host exposure to pesticides may reduce parasitoid attack rate, 49 our results are congruent with studies highlighting a lack of discrimination in terms of parasitoid oviposition behavior between exposed and unexposed hosts. 50,51 Alongside chemical cues, parasitoids use physical traits such as color or shape to locate their hosts. 52,53 Among these physical signals, host locomotion often represents a necessary stimulus for female parasitoids to initiate host contact/attack.…”
Section: Discussionmentioning
confidence: 99%
“…50 In another study, a reduction in the survival of nymphs and reproductive capacity in S. avenae exposed to DON through feeding was observed. 39 Our results confirm the toxic effect of DON even when administered through contact with leaf treatments, with mortality reaching rather high levels at 96 h, comparable to insecticide treatment. Although the ability of S. avenae to transform DON into DON-3G through a detoxification mechanism has been demonstrated, 50 contact with leaf surfaces contaminated with 100 mg L −1 DON still caused a high level of mortality, attributed to the molecule's high cuticular absorption and the limited ability to activate detoxification mechanisms at the tested concentrations.…”
Section: Discussionsupporting
confidence: 80%
“…Unlike other studies on insects related to the toxicity of DON and ENB, this study evaluated the contact effect of the two mycotoxins. 16,39,[42][43][44] The effects of the two mycotoxins on S. avenae were evaluated in terms of mortality at 24-h time intervals after contact of the aphids with the tested mycotoxins. The results showed a clear effect of DON, which at the concentration of 100 mg L −1 exhibited cumulative mortality at 96 h very similar to that caused by exposure to the well-known commercially available insecticide deltamethrin, used at the label concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation